Performance of mustard variety NRCHB-101 through cluster frontline demonstration in Malda, West Bengal - Bhowmik, Paramita; Roy, Rakesh (Indian Farming, 2022)
Mustard variety NRCHB-101 was introduced in adopted villages of Malda Krishi Vigyan Kendra, West Bengal under Cluster Frontline Demonstration on Oilseeds of National Food Security Mission in 110 ha land area during rabi 2019-20. This variety along with appropriate IPM module from the initial stage of cultivation was found superior over the farmer grown varieties with farmers’ practice and gave seed yield of 16.13 q/ha and straw yield of 5.38 q/ha under irrigated condition which was higher over local by 63.57%. This hybrid recorded additional net return and B:C ratio of ` 46,679/ha and 2.10, respectively over locally grown cultivar. Owing to good level of protection from insect and diseases, high yield and high quality parameters, NRCHB-101 with improved IPM package is a suitable choice from farmers’ perspective and the IPM module also maintained soil fertility satisfactorily under old alluvial soil of Malda district of West Bengal.